Kepuasan Kerja Dipengaruhi oleh Lingkungan Kerja, Disiplin Kerja dan Motivasi pada Karyawan PT. Asia Adhitama Shipyard Balikpapan - Istia Vionalita,; Syahril Hasan,; Tutik Yuliani, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this research is to know the influence of Work Environment, Work Discipline, and Motivation to Employee Job Satisfaction of PT Asia Adhitama Shipyard Balikpapan. The type of research used is quantitative research. The sampling technique in this research is saturated sampling with a population of 40 employees so the sample taken is all employees of PT Asia Adhitama Shipyard in Balikpapan City which amounted to 40 employees. Data collection method is done by distributing questionnaires. This research uses multiple linear regression with the help of SmartPLS in processing data. The result of this research shows that work environment, work discipline and motivation variables have influence on job satisfaction of PT Asia Adhitama Shipyard Balikpapan employees.